2020
DOI: 10.3390/su12135394
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Arsenate and Chromate from Ground- and Surface- Waters by Iron-Based Redox Assisted Coagulation

Abstract: Arsenic (As) and chromate (Cr(VI)) contamination of ground and surface waters is a major problem worldwide. Given that a new drinking water limit is anticipated for Cr(VI) and that the limit of arsenic in drinking water is quite low (10 μg/L), there is an urgent need for evaluating technologies that could be efficient for removal of both contaminants simultaneously. In this work, the use of Fe(II) redox assisted coagulation was investigated to simultaneously remove the contaminants of interest. The bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The required ratio of [Fe]/[Cr] for an efficient Cr(VI) removal, at pH 7.2 was slightly above 10, much above the stoichiometry of the reaction between Fe(II) and Cr(VI). Previous relevant studies accomplished in batch mode [16] have demonstrated that the main reason for this difference is the competition of this reaction by oxygen. Oxygen reacts also with Fe(II) and the kinetics of Fe(II) oxidation by oxygen increase as pH increases above pH 7 [17].…”
Section: Resultsmentioning
confidence: 99%
“…The required ratio of [Fe]/[Cr] for an efficient Cr(VI) removal, at pH 7.2 was slightly above 10, much above the stoichiometry of the reaction between Fe(II) and Cr(VI). Previous relevant studies accomplished in batch mode [16] have demonstrated that the main reason for this difference is the competition of this reaction by oxygen. Oxygen reacts also with Fe(II) and the kinetics of Fe(II) oxidation by oxygen increase as pH increases above pH 7 [17].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the main form of Cr in the reacted material is Cr(III) [40]. Obviously, the main Cr removal from the solution mechanism of FeS/LDH involves (1) anion exchange allowing Cr(VI) to enter the interlayered structure of LDH, (2) reduction of Cr(VI) to Cr(III) utilizing reductive properties of Fe 2+ and S 2− , and (3) Fe 3+ and Cr 3+ co-precipitation to remove Cr(T) [34,49]. The schematic diagram of the removal mechanism is shown in Figure 8.…”
Section: Removal Mechanismsmentioning
confidence: 99%
“…precipitation to remove Cr(T) [34,49]. The schematic diagram of the removal mechanism is shown in Figure 8.…”
Section: Removal Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of materials have been applied to remove phosphorus from aqueous solutions, such as zeolite [12], hydrotalcite [13], bentonite [14] and metal oxides [15], it is imperative to develop materials, which are effective in phosphate removal but also can offer multiple contaminant removal, since phosphate is usually present in waters with other pollutants [16]. In our study, we applied materials made up of silica, which we modified with the use of polyethylenimine, to provide plenty of cationic functional groups, which could enhance phosphate removal from waters.…”
Section: Introductionmentioning
confidence: 99%